Optimization of China’s Urban Waste Sorting Policy Pathways from the Public Perspective Under a Multi-Party Cooperation Framework - Yanfei Deng; Sisi Tang; Lin Zhao; Lei Xu (Sustainability, 2026)
China has experienced rapid growth in municipal solid waste generation, highlighting the need to improve the effectiveness of waste sorting governance in urban areas. As the implementation of MSW sorting policies relies heavily on public acceptance and sustained participation, evaluating policy implementation from the public perspective is particularly important, yet comprehensive evaluation frameworks remain limited. This study develops a bottom-up evaluation framework integrating large-scale social media discourse, questionnaire validation, and multi-criteria decision-making. It links LDA topic modeling with policy optimization, constructs 12 multi-actor policy pathways, incorporates DEMATEL-ANP network weighting, applies modified VIKOR for pathway ranking and improvement identification, and verifies robustness using DANP and CRITIC. Results reveal that the Public–Private Partnership model combined with compulsory policies and commissioned property management achieves the highest performance (Pathway P3: management outsourcing PPP + mandatory policy + commissioned property management). Public attitude and participation behavior emerged as central upstream criteria in the influence structure, while P3 remained the top-ranked pathway across DANP- and CRITIC-based VIKOR tests and v = 0.3–0.7. The findings indicate that effective waste sorting requires mandatory rules, professional commissioned property management, convenient facilities, and sustained community support, with pathway-specific improvement directed to the most salient economic, social, and environmental weaknesses.